2006
DOI: 10.2152/jmi.53.292
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials for drug approval: a pilot study of the view of doctors at Tokushima University Hospital

Abstract: The development of new and useful pharmaceutical drugs is essential in order to improve the quality of drug therapeutics. Clinical trials play a central role in drug development. Over time, the clinical trial infrastructure has improved and is now integrating the contribution of clinical research coordinators (CRC). Nevertheless, the attitude of doctors towards clinical trials still favors conventional/historical methodologies. In the present study, we explored the view of doctors towards clinical trials for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…To prepare the questionnaire, we modified and added questions to a questionnaire from a similar study conducted in Tokushima University Hospital [8]. …”
Section: Methodsmentioning
confidence: 99%
“…To prepare the questionnaire, we modified and added questions to a questionnaire from a similar study conducted in Tokushima University Hospital [8]. …”
Section: Methodsmentioning
confidence: 99%
“…We have already reported physicians’ view on registration trials [6], and considered understanding clinical nurses’ awareness of research, including “local” situations, may contribute to the establishment of a clinical research infrastructure. Therefore, we focused on clinical nurses and used questionnaires to survey their status at Tokushima University Hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our previous studies revealed that doctors' views regarding registration trials at Tokushima University Hospital have remained conventional. 4 A clear understanding of the attitude of doctors at networking medical institutions, therefore, may contribute to the establishment of an effective network strategy, and improve the understanding and organization of clinical trials in regional areas. The present survey revealed that 48% of the doctors questioned were familiar with registration trials and their attitude towards participating as investigators in these trials was favourable (87% felt positive).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies that were conducted in 2000 and 2004 at Tokushima University Hospital, we reported that more doctors were familiar with registration trials (66% in 2004 and 84% in 2000) but fewer felt favourable towards participating as investigators (58% in 2004 and in 66% in 2000). 4 Considering that the doctors who responded to the …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation